2012
DOI: 10.1242/dev.078923
|View full text |Cite
|
Sign up to set email alerts
|

The differentiation and movement of presomitic mesoderm progenitor cells are controlled by Mesogenin 1

Abstract: SUMMARYSomites are formed from the presomitic mesoderm (PSM) and give rise to the axial skeleton and skeletal muscles. The PSM is dynamic; somites are generated at the anterior end, while the posterior end is continually renewed with new cells entering from the tailbud progenitor region. Which genes control the conversion of tailbud progenitors into PSM and how is this process coordinated with cell movement? Using loss-and gain-of-function experiments and heat-shock transgenics we show in zebrafish that the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(118 citation statements)
references
References 37 publications
10
106
0
Order By: Relevance
“…3I-L′, white arrowheads). The regulation of msgn1 in the tailbud by FGF signaling has also been demonstrated previously (Fior et al, 2012). Gain of FGF function had the opposite effect, again most notably in the posteriormost domain ( Fig.…”
Section: Fgf Signaling Is Required For Pm Induction From Nmpssupporting
confidence: 82%
See 2 more Smart Citations
“…3I-L′, white arrowheads). The regulation of msgn1 in the tailbud by FGF signaling has also been demonstrated previously (Fior et al, 2012). Gain of FGF function had the opposite effect, again most notably in the posteriormost domain ( Fig.…”
Section: Fgf Signaling Is Required For Pm Induction From Nmpssupporting
confidence: 82%
“…Homozygous tbx16 mutants exhibit greatly expanded ntla expression in the tailbud (Fior et al, 2012;Yabe and Takada, 2012). During tailbud mesoderm induction from NMPs, future mesodermal cells undergo a two-step EMT .…”
Section: Fgf Signaling Is Required For Pm Induction From Nmpsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we showed that msgn1 must be excluded from MPCs in order for mesodermal descendants to join the notochord rather than somites. Expression of msgn1 in cells that will form somites involves positive inputs from T-box transcription factors, canonical Wnt signaling, and FGF signaling, which may only occur at the correct levels in the region of the PWPCs (Fior et al, 2012;Wittler et al, 2007;Yabe and Takada, 2012). Alternatively, the unique signaling environment of the MPCs can turn on the specific expression of transcriptional repressors such as flh, which may inhibit msgn1 expression, similar to its normal role in inhibiting tbx16 (also known as spadetail) expression (Amacher and Kimmel, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…7B,B′). Embryos also appear shorter than their wild-type siblings, which is likely to be due to the ability of msgn1 to promote the differentiation rather than maintenance of PWPCs, which prematurely exhausts this progenitor pool (Fior et al, 2012;Yabe and Takada, 2012). When msgn1 is induced throughout the embryo at the end of gastrulation (bud stage), the notochord ends abruptly and there is a transition to midline somite formation (Fig.…”
Section: Tailbud Notochord Progenitors Are Competent To Become Paraximentioning
confidence: 99%